Anda di halaman 1dari 6

# FIRST ORDER DEFFERENTIAL EQUATION

A.

Definition :
If we have
+ = 0;

## and if we can modify that equation as () = () is called separable

differential equation where we separating the variables.
Example :
1

= 2 = 2 = 2

2.

9 + 4 = 0 9 = 4 9 = 4

3.

1.

2 + 1 + 2 + 1 = 0 2 + 1

= 2 + 1 2 +1 =

1
2 +1

1.

## Separate variables to write the ODE in the form () + () = 0, and

identify the coefficients () and ().

2.

3.

## Solution = () satisfy the implicit general solution formula () +

() = for suitable values of the constant C.

Examples

Solution of = 2 is :
= 2

1
= 2

1
=

ln = 2 + 1
=

2 +

= ; = 1

Solution 2 + 1 + 2 + 1 = 0 ; 0 = 1 is:
2 + 1 + 2 + 1 = 0

1
=
+1

+1

tan = tan +
1

4

## So, the solution of the differential equation above is + =

1
4

or
tan( tan + tan ) = tan

1
4

+

1 = 1

## B. REDUCTION DIFFERENTIAL EQUATION TO SEPARABLE DIFFERENTIAL

EQUATION
Sometimes we find a differential equation with non separable variables but we can be
transformed that equation into separable equation. A differential equation in following
form:

The equation in form above can reduces be a separable form by making transformation or
substitution = where = (). If = , then = + , thus = (/)
+ =

+ =

1
=
=

Examples:
3 2 2

1.

+ 2 + 2 = 0; 1 = 0

Solution :
1) =

(3 2 2 )
2

=2

=2

## Let = where = such that = + .

=

3 2 2
32 2 2
3
1
+ =
+ =
2
2
2
2
2

1
1

1
=

=
1
1
2
2

1
=
2
1

2
=
2 1

ln 2 1 = ln + 1 2 1 =
2
2 1 =

2
> 0 2 1 =

2).

+ 2 + 2
=
; 1 = 0

+ 2 + 2 2

## = = + ,such that we obtain ; + =

+ = + 1 + 2
= 1 + 2
=

1 + 2

ln + 2 + 1 = ln + 2 + 1 = +
2 + 2 =

## since 1 = 0 = 1 So the solution of differential equation above is + 2 + 2 =

Second Way
1

Let = = cos 2 1 + 2 =
then

cos 2

1
cos

sin 2

4 2
=

sin 4 2 cos 4 2

42

4 2 cos 2 4 2

4 2
=

4 2
So, the solution is + 2 + 2 = 2

= ln

+
4 2

++

= ++ + + + + + =

## *) If = = 0 use the transformation + =

**) If 0 use transformation = + ,
= + ,where (, ) is the solution of (, ) from the linear equation system
+ + = 0
+ + = 0
Examples:
Find the solution of the equation below :
1). + 2 + 3 + 2 + 4 1 = 0
2). 2 5 + 3 2 + 4 6 = 0
Solution:
1.

+ 2 + 3 + 2 + 4 1 = 0 = 1, = 2, = 2, = 4

## Such that = 2.2 4.1 = 0 )

Let = + 2 = + 2
+ 2 + 3 + 2 + 4 1 = 0 + 3 + 2 1 = 0
+ 3 + 2 + 1
+3

1
= 0
2

1
1
2 1 + 2 1 = 0
2
2

7
2 1
+
= 0
2
2

7
1 2
=

2
2

7
1
1
1
= 2 2 =
2
2
2
2

7 = 2 +
7 + 2 =
7 = ( + 2)2 + 2 =

2). 2 5 + 3 2 + 4 6 = 0
Solution of SPL 2 5 + 3 = 0 2 4 + 6 = 0 = 1, = 1.
where the transformation are
= + 1 = + 1, = =
then 2 5 + 3 + 2 4 + 6 = 0
2 + 1 5 + 1 + 3 + 2 + 1 4 + 1 + 6 = 0
2 5 + 2 4 = 0

2 5 2 5

=
=
=
()

2 + 4 2 + 4

25

## Equation (*) becomes + = 2+4

2 5 2 4 2 2 7 4 2

=
=

2 + 4
2 + 4

2 + 4

=
2 7 4 2

2 1 + 2

=

4 + 1 + 2

2 + 4

+ 2 + 4
4 + 2 +
=
+
=
=
4 + 1 + 1
1 4 + 2
1 4 + 1
1 4 + 2
4 = 4
2 + = 2

2 8 = 8
2 + = 2

2
2
4
9 = 6, = & = 4 1 + = 4 1 + = 4 1
=
3
3
3
4
2

=
3( 1 4) 3( + 2)

1 1 4
2 + 2

=
3 1 4
3 +2

1
2
ln 1 4 ln + 2 = ln + 1
3
3
1
ln 1 4 + 2 2 = ln + 1
3
1 4 + 2 2 3 = 2
2

14
+ 2 3 =

4 + 2 2 =
1 1 ,
14 1
1 +2 1 =
4 + 3 = 2 3 2
=